ELICITATION TECHNIQUE EMPLOYED BY EFL TEACHERS IN MOTIVATING JUNIOR HIGH SCHOOL STUDENTS TO SPEAK - Kadek Lelyana Rastari; Luh Putu Artini; Ni Putu Astiti Pratiwi; Ni Putu Wiraningsih (Journal of English Language and Culture, 2023)
This study was inspired by the lack of teaching techniques that could accommodate students’ speaking skills as the main indicator determining students’ success in learning English. The elicitation technique could be used by teachers to initiate students to speak during the learning process. A descriptive qualitative method was employed which aimed to investigate the types of elicitation techniques used, the way to implement them, and students’ responses to the elicitation techniques employed by the English teachers in motivating students to speak. There were two English teachers and ten students consisting of seventh and eighth grades involved as the participants in this study. Checklist, classroom observation, interview, and video audio recordings were conducted as the methods of data collection by means of observation checklist, observation sheet, interview guide, as well as video-audio recorders. The data were analyzed based on the category of elicitation techniques proposed by Cross (1992). The findings showed that there were 10 types of elicitation techniques used. Speech Prompts 44.5 (28.7%), WH Short-Answer Question 42.5 (27.4%), dan Yes-No Question 37 (23.9%) were the most frequent types used by the teachers in eliciting students to speak. In addition, it was also revealed that the elicitation techniques were employed by the teachers in all the teaching segments. Eight out of ten students positively responded by feeling motivated to speak in English. This indicated that the elicitation techniques used by the teachers could motivate students to speak in English.